Hubungan Tingkat Pendidikan dengan Perilaku Ibu dalam Pemberian Asidi BPM Ny. Andre Kediri - Latifatun Nasihah (STIKes Patria Husada Blitar, 2015)
Mother's Milk is needed by a baby for a perfect growth. Ironically, in an era of global rapid changes in science and technology, breast-feeding is exclusive often forgotten. Knowledge of Asi Eksklushif very important given to the mother to change the behavior. Many factors affect one's understanding of the exclusive breastfeeding. influenced by the level of education of each individual. Exclusive ation given to each nursing mothers to strengthen the attitude of the mother in breastfeeding. The aim of this study was to analyze the relationship between Education With Mother Behavior in providing breast feeding to the baby. This study uses a correlative analytic design with cross sectional approach. Its population is are all subjects that come midwifery clinic Ny. Andre Kediri, and samples were taken with purposive sampling technique. Data collection using questionnaires, and the data collected is presented in the form of a frequency distribution table and analyzed using logistic regression test. The results showed the greatest level of maternal education is secondary (high school) at 53.8%. , And most of that is 73.1% of behavior is not exclusive breastfeeding mothers to their babies. Logistic regression analysis showed a p-value = 0.067> 0.05 means that H0 and H1 rejected. The results showed no relationship between level of education and mother's behavior in exclusive breastfeeding. The government should improve the comprehensive and continuous education about the importance of breastfeeding and the benefits of exclusive breastfeeding